Synthesis and Characterisation of Reduced Graphene Oxide/Bismuth Composite for Electrodes in Electrochemical Energy Storage Devices. Issue 2 (18th January 2017) - Wang, Jiabin; Zhang, Han; Hunt, Michael R. C.; Charles, Alasdair; Tang, Jie; Bretcanu, Oana; Walker, David; Hassan, Khalil T.; Sun, Yige; Šiller, Lidija
Abstract: A reduced graphene oxide/bismuth (rGO/Bi) composite was synthesized for the first time using a polyol process at a low reaction temperature and with a short reaction time (60 °C and 3 hours, respectively). The as‐prepared sample is structured with 20–50 nm diameter bismuth particles distributed on the rGO sheets. The rGO/Bi composite displays a combination of capacitive and battery‐like charge storage, achieving a specific capacity value of 773 C g −1 at a current density of 0.2 A g −1 when charged to 1 V. The material not only has good power density but also shows moderate stability in cycling tests with current densities as high as 5 A g −1 . The relatively high abundance and low price of bismuth make this rGO/Bi material a promising candidate for use in electrode materials in future energy storage devices. Abstract : Supercapattery composite ! A reduced graphene oxide/bismuth (rGO/Bi) composite is synthesized for the first time using a low temperature (60 °C) polyol process with a short reaction time (3 hours). The rGO/Bi material has high specific capacity. The composite also exhibits moderate stability in cycling tests even at current densities as high as 5 A g −1 .